Effects of phenanthrene on oxidative stress and inflammation in lung and liver of female rats. Issue 1 (27th August 2019) - Ma, Haitao; Wang, Huiling; Zhang, Haojun; Guo, Huizhen; Zhang, Wenwen; Hu, Fengjing; Yao, Yueli; Wang, Dong; Li, Chengyun; Wang, Junling
Abstract: Phenanthrene (Phe) female rat model was established to explore the effects of Phe on oxidative stress and inflammation. The rats were randomly divided into three groups including control (C), low (L), and high (H) group. Phe was supplied to L and H groups at the dosage of 180 mg/kg and 900 mg/kg orally at first day, and with the dose 90 mg/kg and 450 mg/kg by intraperitoneal injection at the last 2 days. The C group was enriched with the same volume of corn oil. The blood, lung, and liver tissues were collected. The superoxide dismutase (SOD), malonaldehyde (MDA), and 8‐hydroxy‐2‐deoxyguanosine (8‐OHdG) were detected to evaluate oxidative stress. The protein and mRNA expressions of interleukin 6 (IL‐6), tumor necrosis factor‐α (TNF‐α), transforming growth factor‐β (TGF‐β), and interleukin 10 (IL‐10) were detected to evaluate inflammation. Further, the forkhead box transcription factor 3 (Foxp3) was analyzed to hint the injury mechanism of inflammation. The results showed SOD and MDA in lung and liver, and serum 8‐OHdG elevated significantly in H groups ( P < .05). Meanwhile, there were significant increases in the protein and mRNA expression of TNF‐α and IL‐6 in lung and liver of H groups ( P < .05). In addition, the protein and mRNA expressions of TGF‐β and Foxp3 were all decreased significantly in both lung and liver of H groups ( P < .05). Results demonstrated that an obvious change of Phe exposure could induce oxidative stress and inflammation in female rats. This is a first pilot study to explore the association between Phe exposure and oxidative stress and inflammation using a female rat model.